Assessing the Future Potential of Industrial Packaging - Bhalani, Rikshit (ATLAS SkillTech University, 2025)
The Internship Report titled "Assessing The Future Potential Of Industrial Packaging" provides a comprehensive overview of my experience as an intern at Pentax Plastics, an innovative HDPE drum and can manufacturing company. The report summarizes the valuable insights and practical knowledge gained during this summer internship program as part of my second-year MBA program at Atlas Skilltech University. Throughout my internship, I actively participated in various aspects of the sales process, including strategy development in target identification, research, outreach, product demonstrations, and pipeline management. Under the guidance of my respected mentors, I navigated the dynamic world of sales and seized the opportunity to connect theoretical concepts with real-world applications. The internship has influenced my professional development and adapted my academic knowledge to the demands of today's business environment. This summary provides insight into the detailed findings and reflections shared in the following sections of the report, allowing readers to understand the value of experiencing this transformative practice at Pentax Plastics.
Project Report on Assessing the Future Potential of Industrial Packaging (2023-2025) Under the Guidance of Prof. Apurva Mehta
Keywords: Industrial Packaging; Pentax Plastics; HDPE drum; target identification; product demonstrations; pipeline management; business environment